Immunogenic evaluation of chimeric recombinant protein against ETEC, EHEC and Shigella - Khalouie, Farzane (Mol Biol Res Commun, 2017)
Diarrheal diseases still remain health problem worldwide and out of many bacteria responsible for, Shigella and pathogenic Escherichia cause the most diarrheas in the world. Shigellacause bacterial dysenteries and shigellosis through invasion where the most effective proteins for pathogenesis is Ipac. Critical virulence protein for ETEC infection is CFA/I with two subunits called cfab and cfae. . Attachment of EHEC is the main step of infection and the protein Intimin plays the key role in this function. Protection against the vast majority of responsible pathogens of diarrheas requires development of the combination vaccine against Shigella, ETEC and EHEC. In the present study, a multisubunitprotein (CII) containing immunologically significant parts of CfaB, IpaC and Intimin was designed. The chimeric gene (CII) was codon optimized and analyzed with different bioinformatic servers, then synthesized and expressed in E. coli. Mice, Guinea pig and, Caco-2 Cell line were used as challenge models for EHEC, shigella and ETEC respectively. The chimeric protein induced significant immune response and therefore could be a suitable vaccine candidate against these three pathogens.